Konstruksi Alat Ukur Kebosanan Adaptif - Arilia, Ulfa; Dutta, Vanessa Bindiya; Al Muniroh, Zannuba Inayatul; Hidayatul Qoyyimah, Nur Rohmah (Flourishing Journal, 2025)
Boredom is a common experience for many individuals, including students pursuing higher education. Boredom, which is always considered negative, can actually serve an adaptive function by encouraging individuals to seek new goals or experiences. Among the many boredom instruments available, none specifically measure adaptive-boredom, prompting researchers to develop a measurement tool based on four aspects formulated by Bench and Lench (2013), namely behavior, cognition, experience, and physiology. The instrument was initially developed with 34 items that were tested for content validity by three expert judges using Aiken's V, resulting in 26 items suitable for testing. The subjects involved were 228 students from all over Indonesia aged 18–25 years (19 males and 209 females). Confirmatory Factor Analysis (CFA) showed that the initial model was not a good fit, so it needed to be modified based on the factor loading values. The final model had 11 items with good model fit indicators (CFI = 0.975; GFI = 0.959; RMSEA = 0.049). The reliability test of the three aspects, namely behavior, cognition, and physiology, showed adequate reliability, while the experience aspect still needed development. The results of the study found that the adaptive boredom measurement tool had a valid and reliable factor structure in most aspects, so that it could be used to measure the tendency of adaptive boredom in students. Abstrak Kebosanan merupakan hal yang umum dialami oleh banyak individu, termasuk mahasiswa yang sedang menempuh pendidikan di perguruan tinggi. Kebosanan yang selalu dianggap negatif, ternyata dapat berfungsi secara adaptif dengan mendorong individu mencari tujuan atau pengalaman baru. Dari banyaknya instrumen kebosanan, belum ada yang spesifik mengukur kebosanan adaptif (adaptive-boredom), sehingga peneliti memiliki tujuan untuk mengembangkan alat ukur berdasarkan empat aspek yang telah dirumuskan Bench dan Lench (2013) yaitu perilaku, kognisi, pengalaman, dan fisiologis. Penyusunan instrumen diawali dengan 34 aitem yang telah diuji validitas konten oleh tiga expert judgement menggunakan Aiken’s V dan menghasilkan 26 aitem layak untuk diuji coba. Subjek yang terlibat sebanyak 228 mahasiswa seluruh indonesia berusia 18–25 tahun (19 Laki-Laki dan 209 Perempuan). Analisis Confirmatory Factor Analysis (CFA) menunjukkan model awal belum fit sehingga perlu modifikasi berdasarkan nilai factor loading. Model final terdapat 11 aitem dengan indikator kecocokan model yang baik (CFI = 0,975; GFI = 0,959; RMSEA = 0,049). Uji reliabilitas tiga aspek yaitu perilaku, kognisi, dan fisiologis memiliki reliabilitas memadai, sedangkan aspek pengalaman masih perlu pengembangan. Hasil penelitian menemukan bahwa alat ukur kebosanan adaptif (adaptive-boredom) memiliki struktur faktor yang valid dan reliabel pada sebagian besar aspek sehingga dapat digunakan untuk mengukur kecenderungan kebosanan adaptif pada mahasiswa.